GERES Project / 2005: New Items for the Construction and Interpretation of Profiency Scale - Lina Kátia Mesquita de Oliveira; Creso Franco; Tufi Machado Soares (Universidad Autónoma de Madrid, 2018)
This article presents a new methodology for the construction and interpretation of scales of cognitive proficiency based on a hypothesis drawn from Item Response Theory that an item is independent and one-dimensional. The data comes from the GERES/2005 Project. Brief descriptions of the project and of the proficiency tests are included with a view to improving understanding of the new methodology for the construction of the scales which, instead of using anchor items, proposes to use the statistics for each item regarding the development of that ability measured by the item to define the θ intervals (proficiency). In this way some of the limits imposed by the normal methodology can be overcome, with gains in precision regarding the stages of development of each ability and in the range of abilities analyzed because there is an ability described on the proficiency scale for each item tested. Following this, a pedagogical analysis of the levels on the GERES project Proficiency Scale is presented in order to describe the abilities shown by pupils at each level of proficiency to enable a qualitative diagnosis of school achievement and a measure of the progress of the pupil over the period assessed.